Metallic sulfide nanoparticles anchored graphene oxide: Synthesis, characterization and reduction of methylene blue to leuco methylene blue in aqueous mixtures. (April 2020) - Dev, Sachin; Singh, Man
Abstract: Oxidizing graphite (Gt) to graphene oxide (GO) through non-explosive oxidizing mixture at 55 °C is reported with high yield. GO was anchored with NiS, ZnS, and CdS metallic sulfide nanoparticles (MSNPs) in 1:1 ratio at 85 °C. MSNPs were obtained by using chloride salts of Ni, Zn, and Cd metals with thiourea in 1:3 ratio in aqueous GO for in situ doping. The GO and MSNPs doped GO (MSNP-GO) were characterized with X-ray diffraction (XRD), FTIR, UV–Vis spectrophotometry, Raman spectroscopy and thermogravimetric analysis (TGA). The GO, CdS-GO, NiS-GO, ZnS-GO had photocatalyzed methylene blue (MB) reduction by 88, 97.22, 79.68, and 89.87% to leuco MB (LMB) colorless, in aqueous medium respectively. Contrary to NiS-GO, the CdS and ZnS increased MB reduction by 9 and 1.87% respectively by weakening intersheet Vander Waals forces of GO for availing surface area. Ni 2+ with 3d 8 catalyzed 8.32% less MB to LMB than Zn 2+ with 3d 10 and Cd 2+ with 4d 10 . MSNPs were uniformly anchored within the 2D GO sheets through sulfide anions (S 2− ) releasing activity for a higher reduction from water and electronically active solvents. MSNP-GO-MB-LMB ventures a novel host-guest chemistry as the MB with sp 2 along with sp 2 -sp 3 hybridizations of GO are photocatalyzed to LMB. MSNP-GO-MB-LMB formulates a multifunctional nanocluster to absorb solar radiation energy and heat contents due to MSNPs-GO interfaces. Likewise ethylene (EB) and propylene blue (PB) could be separated through selective reductions as per their hydrophobicity. Graphical abstract: Figure depicts GO and C-GO synthesis by adopting green routes of chemical activities along with MB adsorption, UV absorption distinguishes C-GO from GO and optimization energies of MB, EB and PB dyes. Langmuir isotherm for MB adsorption by C-GO contrary to a linear adsorption by GO is fitted. Image 1 Highlights: Graphite was functionalized to graphene oxide. GO had in situ anchored metallic sulfide nanoparticles. MSNP-GO had reduced 97% methylene blue. Intersheet distance in GO increased compared to Gt. Intersheet vander Waals forces accommodated MSNPs.